Unveiling polyoxometalate redox properties at the nanoscale - Volatron, Florence; Izzet, Guillaume; Vuillaume, Dominique; Proust, Anna (Comptes Rendus. Chimie)
Polyoxometalates (POMs) are molecular nano-oxides of early transition metals. As molecular oxides, they are endowed with remarkable redox properties, combining the reducibility of bulk metal oxides and the high versatility of molecular species. They undergo successive, reversible, and highly adjustable mono- (or multi-) electronic reduction processes within a narrow range of potentials. Furthermore, POMs are polyanions, with counter cations playing a crucial role, beyond ensuring charge neutrality. As the missing link between extended oxides, commonly found in microelectronics, and conventional organic or organometallic molecules, POMs have attracted ever-increasing interest in the field of nanoelectronics. They hold promise as charge storage nodes in multilevel nonvolatile memories and resistive switching devices, areas of interest currently boosted by the development of neuromorphic computing. In this context, we have been exploring various strategies to immobilize POMs onto electrodes with the aim of improving the control of the molecules/electrode interface. We have been investigating electron transport properties across POM-based molecular nanojunctions to establish relationships among the POM molecular structure, the electronic structure, and the properties of POM devices (e.g., conductance, switching). Additionally, we have demonstrated that we can commute the redox state of a POM layer by exposure to light or by applying an electric field, opening up new opportunities to stimuli-responsive devices.